REGENERATION OF RHENIUM USING STRONG BASE ANION EXCHANGERS - HURA АNNA; SKNAR, YURI; KOZHURA, OLEG; HOLICHENKO, OLEKSANDR; KOZHURA, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
During the war and in the post-war period, an important applied task is the processing of scrap military equipment and the regeneration of precious metals, in particular rhenium. The relevance of the work is due to the strategic importance of this metal for the defense complex of Ukraine, since alloys based on it are characterized by extremely high physical and mechanical properties and are used as a structural material in gas turbine equipment of aviation equipment. In the presented work, a technique for extracting and concentrating rhenium from diluted complex solutions obtained during the disposal of spent rhenium-containing materials was developed. The extraction of rhenium from the solution was carried out using spent strongly basic anionites Amberlite HPR 550 and Amberlite IRA 402 with a styrenedivinylbenzene matrix. The strongly basic anionites used in the work are used at domestic nuclear power plants for water desalination. After a partial loss of exchange capacity, such anionites become unusable for their intended purpose and must be disposed of. At the same time, these anions retain sorption properties and can be used for selective extraction of perrhenate anion from leaching solutions of superalloy scrap. The sorption properties of anionites were investigated using model solutions obtained during the extraction of rhenium-containing compounds from spent materials of research work, and solutions of leaching of scrap aircraft engine turbine blades, which contained 3.49% rhenium. The studied anionites showed high selectivity in relation to rhenium capture. Further processing of anionites with sorbed perrhenate anion consisted in pyrometallurgical processing in the presence of lime. The optimal burning conditions of the anionite (after sorption)-lime mixture are proposed. The mass ratio of anionite and lime is 1:4. Decomposition of such a mixture is carried out at a temperature of 900 °C for 4 hours. Under these conditions, the styrenedivinylbenzene matrix of the anionite decomposes and calcium perrhenate is released. The degree of rhenium extraction carried out according to the proposed method is about 97%, which makes it possible to recommend the use of strongly basic spent anionites for the selective isolation of rhenium and the production of high-purity rhenium compounds.